Using a multi-criteria decision-matrix framework to assess the recovery potential of coral reefs in the South Western Indian Ocean - Florian Jouval; Mehdi Adjeroud; Anne Catherine Latreille; Lionel Bigot; Sophie Bureau; Pascale Chabanet; Patrick Durville; Simon Elise; David Obura; Valeriano Parravicini; François Guilhaumon; Simon Brandl; et al. (Ecological Indicators, 2023)
Over the last two decades, coral reefs have experienced dire declines due to intensifying anthropogenic disturbances and climate change. Defining and quantifying coral reef resilience now represents a critical management objective, but there is still little consensus on the approach and the indices to be used. In this study, we develop a multi-factor reef recovery index based on the Technique for Order Preference by Similarity to an Ideal Solution (TOPSIS) method to assess the vulnerability of several insular coral reefs in the South Western Indian Ocean (SWIO) from 2016 to 2018. We showed, that in the wake of a regional bleaching event in 2016, the most isolated reefs of Europa, which is characterized by low direct human impact had the highest recovery potential. On the contrary, islands that are more prone to direct human influence (i.e., La Reunion and Rodrigues) displayed the lowest recovery potential.